Communities and service providers address access to perinatal care in postconflict Northern Uganda: socialising evidence for participatory action. Issue 2 (17th March 2021) - Belaid, Loubna; Atim, Pamela; Atim, Eunice; Ochola, Emmanuel; Ogwang, Martin; Bayo, Pontius; Oola, Janet; Wonyima Okello, Isaac; Sarmiento, Ivan; Rojas-Rozo, Laura; Zinszer, Kate; Zarowsky, Christina; et al.
Abstract : Objectives: Describe participatory codesign of interventions to improve access to perinatal care services in Northern Uganda. Study design: Mixed-methods participatory research to codesign increased access to perinatal care. Fuzzy cognitive mapping, focus groups and a household survey identified and documented the extent of obstructions to access. Deliberative dialogue focused stakeholder discussions of this evidence to address the obstacles to access. Most significant change stories explored the participant experience of this process. Setting: Three parishes in Nwoya district in the Gulu region, Northern Uganda. Participants: Purposively sampled groups of women, men, female youth, male youth, community health workers, traditional midwives and service providers. Each of seven stakeholder categories included 5–8 participants in each of three parishes. Results: Stakeholders identified several obstructions to accessing perinatal care: lack of savings in preparation for childbirth in facility costs, lack of male support and poor service provider attitudes. They suggested joining saving groups, practising saving money and income generation to address the short-term financial shortfall. They recommended increasing spousal awareness of perinatal care and they proposed improving service provider attitudes. Participants described their own improved care-seeking behaviour and patient–provider relationships as short-term gains of the codesign. Conclusion: Participatory service improvement is feasible and acceptable in postconflict settings like Northern Uganda. Engaging communities in identifying perinatal service delivery issues and reflecting on local evidence about these issues generate workable community-led solutions and increases trust between community members and service providers.